Effects of Calcium-Oxide-Modified Biochar on the Anaerobic Digestion of Vacuum Blackwater - Ping Fa Chiang; Teng Ling Zhang; Abdulmoseen Segun Giwa; Ndungutse Jean Maurice; Mugabekazi Joie Claire; Nasir Ali; Ehtisham Shafique; Mohammadtaghi Vakili (Molecules)
The increasing global population and urbanization have led to significant challenges in waste management, particularly concerning vacuum blackwater (VBW), which is the wastewater generated from vacuum toilets. Traditional treatment methods, such as landfilling and composting, often fall short in terms of efficiency and sustainability. Anaerobic digestion (AD) has emerged as a promising alternative, offering benefits such as biogas production and digestate generation. However, the performance of AD can be influenced by various factors, including the composition of the feedstock, pH levels, and the presence of inhibitors. This review investigates the effects of calcium oxide (CaO)-modified biochar (BC) as an additive in AD of VBW. Modifying BC with CaO enhances its alkalinity, nutrient retention, and adsorption capacity, creating a more favorable environment for microorganisms and promoting biogas production, which serves as a valuable source of heat, fuel and electricity. Additionally, the digestate can be processed through plasma pyrolysis to ensure the complete destruction of pathogens while promoting resource utilization. Plasma pyrolysis operates at extremely high temperatures, effectively sterilizing the digestate and eliminating both pathogens and harmful contaminants. This process not only guarantees the safety of the end products, but also transforms organic materials into valuable outputs such as syngas and slag. The syngas produced is a versatile energy carrier that can be utilized as a source of hydrogen, electricity, and heat, making it a valuable resource for various applications, including fuel cells and power generation. Furthermore, the slag has potential for reuse as an additive in the AD process or as a biofertilizer to enhance soil properties. This study aims to provide insights into the benefits of using modified BC as a co-substrate in AD systems. The findings will contribute to the development of more sustainable and efficient waste management strategies, addressing the challenges associated with VBW treatment while promoting renewable energy production.